Improving police conceptual knowledge of Mexico's law on cannabis possession: Findings from an assessment of a police education program. (5th December 2018) - Mittal, Maria L.; Artamonova, Irina; Baker, Pieter; Strathdee, Steffanie A.; Cepeda, Javier; Bañuelos, Arnulfo; Morales, Mario; Arredondo, Jaime; Rocha‐Jimenez, Teresita; Clairgue, Erika; Bustamante, Elaine; Patiño, Efrain; et al.
Abstract : Background and Objectives: Policing practices do not reflect recent decriminalization of drug possession in Mexico. We assessed knowledge of cannabis law as part of a police education program (PEP) post‐drug law reform in Tijuana. Methods: Officers took pre‐/post‐PEP surveys; random subsample ( n = 759) received follow‐up assessments. Longitudinal logistic regression (pre‐, post‐, 3‐months post‐PEP) measured knowledge of cannabis law. Results: PEP increased conceptual knowledge of cannabis law from baseline to post‐training (AOR = 56.1, CI: 41.0–76.8) and 3 months post‐PEP (AOR = 11.3, CI: 9.0–14.2). Conclusion and Scientific Significance: PEPs improve police knowledge of cannabis law. Reforms should be bundled with PEPs to improve policy implementation. (Am J Addict 2018;XX:XX–XX).